Reactive MgO as alkaline activator in slag/fly ash-based strain-hardening cementitious composites for cementless marine engineering - Long Liang; Yunqi Jiang; Xudong Tang; Jie Xiao; Lingfei Liu (Case Studies in Construction Materials)
A novel category of polyethylene (PE) fiber-reinforced strain-hardening reactive MgO-activated slag/fly ash composites (SH-RMGC) with ultra-high ductility is developed in this study. The developed SH-RMGC carried a compressive strength of 17–50 MPa, a tensile strength of 3–8 MPa, and a tensile strain capacity exceeding 7 %. Results showed that a lower water-to-binder (w/b) ratio resulted in higher compressive strength and tensile strength. With increasing MgO content, the matrix fracture toughness, compressive strength, tensile strength, and strain energy density of SH-RMGC increased, while the ultra-high tensile strain capacity remained. The most robust strain-hardening performance was recorded in SH-RMGC with 20 % MgO. The mechanism of ultra-high tensile ductility was illustrated based on a micromechanical model. The impacts of MgO contents on the chemical characterization of matrix were investigated to understand the gained mechanical performance of SH-RMGC. The primary hydration products of matrix were C-A-S-H, brucite, and hydrotalcite-like, and higher MgO content led to higher hydration reaction degree. The reduced Al/Si ratio of C-A-S-H and the enhanced Mg/Al ratio of hydrotalcite-like were found with the addition of MgO, resulting in the refined microstructure with reduced porosity. Additionally, the developed SH-RMGC showed better material sustainability than the existing alkali-activated/cement-based counterpart. This advanced material holds the potential for extended application in marine engineering.